Robotic Versus Laparoscopic Liver Resection: A Nationwide Propensity Score Matched Analysis - Gabriela Pilz da Cunha, MD; Jasper P. Sijberden, MD, PhD; Susan van Dieren, PhD; Paul Gobardhan, MD, PhD; Daan J. Lips, MD, PhD; Türkan Terkivatan, MD, PhD; Hendrik A. Marsman, MD, PhD; Gijs A. Patijn, MD, PhD; Wouter K. G. Leclercq, MD, PhD; Koop Bosscha, MD, PhD; J. Sven D. Mieog, MD, PhD; Peter B. van den Boezem, MD, PhD; et al. (Annals of Surgery Open)
Objective:. To compare nationwide outcomes of robotic liver resection (RLR) with laparoscopic liver resection (LLR). Background:. Minimally invasive liver resection is increasingly performed using the robotic approach as this could help overcome inherent technical limitations of laparoscopy. It is unknown if this translates to improved patient outcomes. Methods:. Data from the mandatory Dutch Hepatobiliary Audit were used to compare perioperative outcomes of RLR and LLR in 20 centers in the Netherlands (2014–2022). Propensity score matching (PSM) was used to mitigate selection bias. Sensitivity analyses assessed the impact of the learning curve (≥50 procedures for LLR and ≥25 procedures for RLR), concurrent noncholecystectomy operations, high-volume centers, and conversion on outcomes. Results:. Overall, 792 RLR and 2738 LLR were included. After PSM (781 RLR vs 781 LLR), RLR was associated with less blood loss (median: 100 mL [interquartile range (IQR): 50–300] vs 200 mL [IQR: 50–500], P = 0.002), less major blood loss (≥500 mL,18.6% vs 25.2%, P = 0.011), less conversions (4.9% vs 12.8%, P < 0.001), and shorter hospital stay (median: 3 days [IQR: 2–5] vs 4 days [IQR: 2–6], P < 0.001), compared with LLR. There were no significant differences in overall and severe morbidity, readmissions, mortality, and R0 resection rate. Sensitivity analyses yielded similar results. When excluding conversions, RLR was only associated with a reduction in reoperations (1.1% vs 2.7%, P = 0.038). Conclusion:. In this nationwide analysis, RLR was associated with a reduction in conversion, blood loss and length of hospital stay without compromising patient safety, also when excluding a learning curve effect. The benefits of RLR seem to be mostly related to a reduction in conversions.